2022
DOI: 10.1111/cns.13895
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine pathway metabolites and therapeutic response to olanzapine in female patients with schizophrenia: A longitudinal study

Abstract: ness, which exhibits heterogeneity in psychotic symptoms, clinical response to antipsychotic medication, and side effects. 1,2 Atypical antipsychotics are now considered to be the first-line treatment of SZ. 3 However, there are still some patients with SZ who do not respond adequately to antipsychotic medication because the precise

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“… 621 Previous report has shown that after 4 weeks of olanzapine monotherapy in schizophrenic patients, methyl n-methylaminobenzoate as response biomarkers in the kynurenine pathway is associated with treatment outcomes. 622 Metabolic profile alteration to molecular phenotype of psoriasis vulgaris patients showed that SM (d16:1/16:1) and Cer (d18:1/18:0) correlated with the biochemical indicators and could contribute to precision treatment. 623 Another study used metabolomic profiling and small metabolites (N-methylisoleucine, nornicotine, 2,3-dihydroxybutanoic acid) were able to discriminate rheumatoid arthritis patients with early response to methotrexate therapy.…”
Section: Enabling Precision Treatmentmentioning
confidence: 97%
“… 621 Previous report has shown that after 4 weeks of olanzapine monotherapy in schizophrenic patients, methyl n-methylaminobenzoate as response biomarkers in the kynurenine pathway is associated with treatment outcomes. 622 Metabolic profile alteration to molecular phenotype of psoriasis vulgaris patients showed that SM (d16:1/16:1) and Cer (d18:1/18:0) correlated with the biochemical indicators and could contribute to precision treatment. 623 Another study used metabolomic profiling and small metabolites (N-methylisoleucine, nornicotine, 2,3-dihydroxybutanoic acid) were able to discriminate rheumatoid arthritis patients with early response to methotrexate therapy.…”
Section: Enabling Precision Treatmentmentioning
confidence: 97%